Assessing HIV provider knowledge, screening practices, and training needs for HIV-associated neurocognitive disorders. A short report. Issue 4 (3rd April 2021) - Gouse, Hetta; Masson, Catherine J.; Henry, Michelle; Marcotte, Thomas D.; London, Leslie; Kew, Greg; Rourke, Sean; Robbins, Reuben N.
ABSTRACT: Management of HIV-associated neurocognitive disorders (HAND) is becoming increasingly important with HIV-positive people living normal life spans. We aimed to establish the level of HAND awareness among doctor and nurse occupational health practitioners, screening used to detect impairment, factors limiting screening for HAND, and training needs. One-hundred-and-five members of the nursing and physician professional societies for occupational health practitioners in South Africa and Occupational Health Departments at five South African universities responded to an email invitation to complete an online survey addressing demographics, HAND knowledge, screeners being used to screen for HAND and related training needs. While 80% had heard of HAND, few (13.3%) were aware of the Frascati criteria. Only 2% had received training addressing HAND; 11.4% screened for HAND; 45.7% did not know what screening tool to us; 80% preferred spending <15 min on screening. The largest obstacle to screening was lack of expertise (77.1%) but 77.3% thought it important to screen for HAND. 94.3% wanted screening training. Health providers are poorly informed about HAND and lack expertise and tools to screen for HAND in their treatment programs. While few had relevant training, they recognize the importance of screening for HAND in the workplace and desire training.